Work Engagement as a Moderating Factor between Positive Attitude toward Smart Working and Job and Life Satisfaction - Andrea Zammitti; Angela Russo; Paola Magnano; Maria Guarnera (MDPI AG, 2022)
Attitude toward smart working reflects feelings of favorableness towards this object; attitudes influence intentions, which in turn guide behaviors. Recent research confirms the positive influence that attitude toward smart working has on expected usage of it. Despite a direct influence, other factors could interact in the context of opportunities for ICT usage for teleworkers; among these factors, work engagement stands out. In turn, work engagement influences the perception of job satisfaction and life satisfaction. Considering that literature suggests that among the antecedents of work engagement are attitudes, the present study analyzes the role of positive attitude towards smart working on work engagement, and consequently on job satisfaction and on life satisfaction, hypothesizing that work engagement could mediate between positive attitude towards smart working and job and life satisfaction. The participants were 342 workers (115 males and 227 females) in private and public organizations, aged 24 to 66 years. The results showed that a positive attitude towards smart working, along with work engagement as a mediator, positively influences job satisfaction and life satisfaction. This means that employers and human resources managers (HRM) can organize training sessions to enhance the positive attitude toward smart working and this can help workers feel more engaged and satisfied.